Evaluating Iraqi private banks using the bank loan pricing model: An applied study of a sample of banks listed on the Iraq Stock Exchange (Entrepreneurship Journal for Finance and Business, 2021)
The process of pricing bank loans is one of the most important sources for the bank’s revenues, as loans represent a large part of the bank’s assets. The research aims to measure and know the impact of bank loan pricing indicators on credit risk. When the bank sets a high interest rate, this leads to a loss of customers by going to other banks to obtain loans, and if a low interest rate is set, this leads to a loss for the bank. Therefore, banks should use modern methods of pricing bank loans. The research community represents the banks listed in the market. Iraq Stock Exchange. As for the research sample, it consisted of 8 banks that were selected from among 24 banks listed on the Iraq Stock Exchange that meet the research requirements, and for the period (2006-2015), and a set of financial indicators were used (return on net funds used, weighted average cost of capital, Z-Score Profitability objective) Measurable research variables .